Does the Health and Safety at Work Act 2015 Apply to Roads? - King, Murray (Victoria University of Wellington Law Review, 2016)
This article examines how far the Health and Safety at Work Act 2015 applies to roads. Road authorities have substantial control over the safe use of their roads and, as roads are a product of work, it might be expected that the Act applies to any deficiencies in that work that create harm, as it does to most areas of the economy. But the Act can be read in a way that limits its applicability to actions that cause harm much later and indeed to public safety in general. The article analyses some key sections of the Act to see how far their duties might extend to road authorities. It concludes that while there is some room for doubt, the Act is capable of supporting a prosecution of a road authority, especially in relation to a work-use vehicle. In addition, the so-called "upstream duties" on designers and others could well create a liability for the authorities. The article nevertheless proposes reforms to clarify the liability.